Números fracionários no livro didático do 5º ano do Ensino Fundamental: um estudo praxeológico - Correia, Edna Marcia Okuma (2022)
The present research reports a bibliographic study involving textbooks. The research involved the analysis of 5th Year mathematics textbooks, used in a municipal school in the city of Franco da Rocha. The research is justified from the difficulties presented by teachers and students in relation to the teaching and learning of fractional numbers. The methodological procedures adopted were the exploration of the chosen Official Documents, with the analysis process based on the Anthropological Theory of Didactics (TAD) and supported by the concepts of fractional numbers proposed by Kieren, focusing on the National Common Curricular Base (BNCC) . In this context, the objective of the research was to analyze the praxeologies of the activities on fractional numbers proposed in the mathematics textbooks, verifying if these praxeologies have the potential to prepare the student for the construction of the concept of fractional numbers. The main result obtained with the research was the finding that textbooks prepare students to understand the concepts of fractional numbers, although these concepts are identified according to the technique of solving each task, which present praxeologies with implicit and explicit situations. in which, even if this task is contained in the utterance, students must make these interpretations. The subtitles of the chapters on the contents of fractional numbers and the activities presented, exemplifying how to proceed in solving the tasks, not encouraging students to make discoveries and explore the solving techniques alone, and the teacher should expand these discussions and present differentiated activities such as own books recommend in their guidelines. The fractional number conceptions identified in the activities have predominantly approached the part-whole conception in relation to other conceptions, with emphasis on the repetition of procedures to try to achieve student learning